2006
DOI: 10.1159/000096157
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Shunt Closure via the Lumen of an Intrahepatic Portal Aneurysm

Abstract: Background/Aims: A surgical shunt closure via the lumen of an intrahepatic portal aneurysm was successfully performed in a 70-year-old Japanese woman with hepatic encephalopathy due to hyperammonemia. She had a 4-month history of repeated hepatic encephalopathy which persisted after treatment with oral medicine. Color Doppler ultrasonography and computed tomography revealed a cystic peripheral portal aneurysm, 4 cm in diameter, connecting the posterior branch of the portal vein to the short hepatic vein in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This is largely due to the difficulty in obtaining satisfactory anatomical exposure, adequate proximal and distal vascular control, the often friable nature of the portal vein and the highly variable rates of long-term portal vein patency in patients undergoing repair. 6,17,18 Not surprisingly, a recent metanalysis of 96 case reports of PVAs reported a postoperative mortality of 17.5% in patients undergoing surgical repair highlighting the gravity and high cost of an operative intervention for this condition. 6,15,19,20 Observant management has been previously described in some reports, mainly reserved for asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is largely due to the difficulty in obtaining satisfactory anatomical exposure, adequate proximal and distal vascular control, the often friable nature of the portal vein and the highly variable rates of long-term portal vein patency in patients undergoing repair. 6,17,18 Not surprisingly, a recent metanalysis of 96 case reports of PVAs reported a postoperative mortality of 17.5% in patients undergoing surgical repair highlighting the gravity and high cost of an operative intervention for this condition. 6,15,19,20 Observant management has been previously described in some reports, mainly reserved for asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intrahepatic PV shunts can be treated using surgical ligation or with embolisation via the percutaneous transhepatic portal vein approach or transileocolic vein approach under small laparotomy. 9 , 10 PV shunt embolisation using an AVP II from a percutaneous transjugular or transfemoral venous approach has not been reported, but Lee et al 10 previously reported embolisation of a PV shunt using an AVP II via a transhepatic approach. First, they tried to approach the portal side of the PV shunt from the percutaneous transjugular approach, but it was impossible.…”
Section: Discussionmentioning
confidence: 99%